Effect of various radical transfers and scavengers on the transformation of phenol over UV irradiated TiO2 - Molnár Milán (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
The influence of a radical scavenger methanol (MeOH) and tert-butanol (t-BuOH)) on the transformation rate and radical set during heterogeneous photocatalytic transformation of a simple model compound, phenol (PhOH, 1.0×10-4 mol L-1 ) is discussed in this study. PhOH solutions were treated in the presence of 5.0×10-1 mol L-1 MeOH and t-BuOH under deoxygenated and O2-saturated reaction conditions. The rate of transformation of PhOH increased significantly in the presence of dissolved O2. The radical scavenger materials used strongly reduced the rates of transformation of PhOH both in O2 saturated and O2-free solutions.